Astyanax pampa (Characiformes, Characidae), a new species from the southernmost boundary of the Brazilian subregion, Argentina - Casciotta, Jorge Rafael (2005)
Astyanax pampa sp. n., the new species of characid described herein, is known from arroyo Las Mostazas, an Atlantic Ocean drainage, and the lower rio Colorado basin. Astyanax pampa sp. n. is distinguished from all other Astyanax species by the possession of 17-20 branched anal-fin rays, one maxillary tooth unicuspidate to tricuspidate, short anal-fin base (24.2-30.3% of SL), and long caudal peduncle (10.5-12.7% of SL).